2017
DOI: 10.1007/s10803-017-3240-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Coping Styles, Stress Levels, and Time Use in Mothers of Children with Autism Spectrum Disorders: Comparing Single Versus Coupled Households

Abstract: This study aimed to examine the influence of differences in household status on the parental stress, coping, time use and quality of life (QoL) among mothers of children with autism spectrum disorders. Forty-three single and 164 coupled mothers completed the survey. Data were analysed using multivariate logistic regression. We found that single mothers were 1.05 times more likely to report lower levels of environmental QoL. Whilst they were 1.73 times more likely to use acceptance coping style, this associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 91 publications
2
17
0
1
Order By: Relevance
“…Hence, generalisation of study findings to fathers, lower socioeconomic populations, and parents living in major cities may be limited. However, participants in this study are likely to be representative of those who are most likely to use the TOBY app and other ICT interventions, given mothers in families of a child with ASD are more likely to adopt primary caregiver roles, such as delivering home-based interventions like the TOBY app, compared to families without children with ASD (McAuliffe, Cordier, Vaz, Thomas, & Falkmer, 2017;Nealy, O'Hare, Powers, & Swick, 2012) Finally, although the primary researcherthe interviewerdeclared no conflict of interest with the TOBY app at the beginning of each interview, due to resourcing issues, the primary researcher conducted 20% of the assessments in the RCT. Participants in this study could perceive a conflict of interest and tailor their responses accordingly.…”
Section: Limitationsmentioning
confidence: 99%
“…Hence, generalisation of study findings to fathers, lower socioeconomic populations, and parents living in major cities may be limited. However, participants in this study are likely to be representative of those who are most likely to use the TOBY app and other ICT interventions, given mothers in families of a child with ASD are more likely to adopt primary caregiver roles, such as delivering home-based interventions like the TOBY app, compared to families without children with ASD (McAuliffe, Cordier, Vaz, Thomas, & Falkmer, 2017;Nealy, O'Hare, Powers, & Swick, 2012) Finally, although the primary researcherthe interviewerdeclared no conflict of interest with the TOBY app at the beginning of each interview, due to resourcing issues, the primary researcher conducted 20% of the assessments in the RCT. Participants in this study could perceive a conflict of interest and tailor their responses accordingly.…”
Section: Limitationsmentioning
confidence: 99%
“…People living in LDP areas may lack viable formal support options, such as limited access to: adequately trained support professionals, mental health services, and information, and increased travel time to obtain necessary supports due to having to travel vast geographical distances. These factors may restrict parents' ability to adopt problem-focused and positive coping strategies and encourage the use of avoidant coping strategies (Hoogsteen & Woodgate, 2013a;Lai et al, 2015;McAuliffe et al, 2017;McAuliffe et al, 2016).…”
Section: Copingmentioning
confidence: 99%
“…Furthermore, there is evidence to suggest that coping strategies used by parents of children with ASD could be different when compared to parents of typically developing children or children with other disabilities, due to the differences in social environments (e.g., poorer social supports and limited access to service) often experienced by this group (Hastings et al, 2005;Lai et al, 2015). Few studies have defined and categorised different types of coping strategies used by parents who have a child with ASD (Benson, 2010;Hastings et al, 2005;McAuliffe, Cordier, Vaz, Thomas, & Falkmer, 2017) and none have done so with families living in regional or remote areas in the Australian context. It is plausible that people living in regional areas in Australia may exhibit different coping mechanisms due to the unique context in which they live, such as limited social support and poorer access to services.…”
mentioning
confidence: 99%
“…The result revealed that although mothers acknowledge the attractiveness of work, they can only make sacrifices to assume the role of a mother. According to Mcauliffe et al, 29 single mothers who have children suffering from autism confronted obvious financial disadvantages as a consequence of inadequate employment opportunities and job security policies. Hodgetts et al 30 evaluated potential outcomes of professional support services for mothers of autistic children.…”
Section: Indirect Costs For Parents Of Children With Autismmentioning
confidence: 99%